2010
DOI: 10.3922/j.psns.2010.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Left-right judgment of haptic stimuli representing the human hand.

Abstract: The handedness recognition of visually perceived body parts engages motor representations that are constrained by the same biomechanical factors that limit the execution of real movements. In the present study, we used small plastic cutouts that represented the human hand to investigate the properties of mental images generated during their haptic exploration. Our working hypothesis was that any handedness recognition task that involves body parts depends on motor imagery. Forty-four blindfolded, right-handed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
2
5
1
Order By: Relevance
“…In line with previous findings regarding mental rotation of haptic (Kitada et al, 2009;Rangel et al, 2010) and visual hand stimuli (Cooper & Shepard, 1975;Marmor & Zaback, 1976;Sekiyama, 1982), we found that, for both sensory modalities, a longer RT was associated with a greater disparity of the hand's upright orientation. Such a result is typical for mental rotation of body parts (Cooper & Shepard, 1975;de Lange et al, 2006;Rangel et al, 2010;Vingerhoets et al, 2002) and is assumed to reflect the influence of biomechanical constraints on imagined hand movements (Schwoebel et al, 2001). The present results are consistent with previous findings showing shorter RT for the mental rotation of visually-versus haptically-presented hands (Kitada et al, 2009;Rangel et al, 2010).…”
Section: Behavioral Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous findings regarding mental rotation of haptic (Kitada et al, 2009;Rangel et al, 2010) and visual hand stimuli (Cooper & Shepard, 1975;Marmor & Zaback, 1976;Sekiyama, 1982), we found that, for both sensory modalities, a longer RT was associated with a greater disparity of the hand's upright orientation. Such a result is typical for mental rotation of body parts (Cooper & Shepard, 1975;de Lange et al, 2006;Rangel et al, 2010;Vingerhoets et al, 2002) and is assumed to reflect the influence of biomechanical constraints on imagined hand movements (Schwoebel et al, 2001). The present results are consistent with previous findings showing shorter RT for the mental rotation of visually-versus haptically-presented hands (Kitada et al, 2009;Rangel et al, 2010).…”
Section: Behavioral Resultssupporting
confidence: 92%
“…Although similar findings on response time have been reported in the context of both visually- (Chen et al, 2019;Cooper & Shepard, 1975;Ionta et al, 2007;Parsons, 1994;Sekiyama, 1982) and haptically-based mental rotation of hands (Kitada et al, 2010;Rangel et al, 2010), the neural differences between haptically-and visually-mediated mental rotation of hands are not yet fully understood. Since the relative weighting of the type of imagery in mental rotation of hands may result in distinct patterns of brain activity, our null hypothesis is that mental rotation of both visually-and haptically-presented hands triggers the same type of mental imagery, leading to similar patterns of brain activity.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Research in hand laterality tasks complements the findings reported above by suggesting that right-handers are faster to identify right hands than left hands. Left-handers show a reversed pattern but tend to show no facilitation for either hand (see [30] [31] ). Additionally, the evidence indicates that left-handers are less lateralised than right-handers.…”
Section: Introductionmentioning
confidence: 99%
“…In the Hand group in which the participants considered the stimulus to be their own hands, the dorsal view of their hand yielded faster responses than the palm view (Lameira, Guimarães-Silva, Ferreira, WerneckGalvão, Pereira Jr, & Gawryszewski, 2008b;Lameira et al, 2009;Parsons, 1994;Rangel et al, 2010). This effect supports the finding that the amount of time used to determine the laterality of a hand figure is reliably influenced by the actual posture of the responding body part during the task (Jeannerod, 1994;Jeanerod & Decety, 1995;Lameira et al, 2008a;Lameira et al, 2009;Mercier, Aballea, Vargas, Paillard, & Sirigu, 2005;Parsons, 1987Parsons, , 1994Parsons & Fox, 1998;Sirigu & Duhamel, 2001;Vargas, Oliver, Craighero, Fadiga, Duhamel, & Sirigu, 2004).…”
Section: Discussionmentioning
confidence: 99%